PENGARUH PENGAWASAN TERHADAP DISIPLIN KERJA KARYAWAN PADA PT BANK HSBC CABANG PEKANBARU - Nurhayana, Nurhayana (Eko dan Bisnis: Riau Economic and Business Review, 2024)
This research aims to determine the effect of supervision on employee work discipline at PT Bank HSBC Pekanbaru Branch. The types of data used in this research are qualitative data and quantitative data. The population in this study was all employees, totaling 34 respondents. The sample in this study was 34 employees or respondents. Data analysis techniques use analytical assumption tests, simple linear regression analysis and t statistical tests. Research data was collected from respondents and analyzed using linear regression and hypothesis testing. The results of the research show that supervision has a positive and significant influence on work discipline, with a t value of (3.129) and the magnitude of the influence of supervision on work discipline seen from the coefficient of determination test is 0.234 or 23.4% while the remaining 76.6% is influenced by other variables that are ignored or not. examined in this research.